Microwave Assisted Synthesis of N-Substituted-7-hydroxy-4-methyl-2-oxoquinolines as Anticonvulsant Agents - P. Y. Pawar; P. M. Gaikwad; P. H. Balani (E-Journal of Chemistry)
The reaction of resorcinol with ethylacetoacetate yielded the 7-hydroxy-4-methyl coumarin (1), which on treatment with benzidine gives 1-(4ʹ-amino-biphenyl-4-yl)-7-hydroxy-4-methyl-1H-quinolin-2-one (2). 1-{4ʹ-[(Substituted benzylidene)-amino]-biphenyl-4-yl}-7-hydroxy-4-methyl-1H-quinolin-2-one (3a-j) were obtained by reacting 1-(4ʹ-amino-biphenyl-4-yl)-7-hydroxy-4-methyl-1H-quinolin-2-one (2) with different substituted aromatic aldehydes in presence of glacial acetic acid by microwave irradiation. The compound 1-{4ɴ-[(substituted benzylidene)-amino]-biphenyl-4-yl}-7-hydroxy-4-methyl-1H-quinolin-2-one (3a-j) on cyclization with chloro acetyl chloride in presence of triethylamine as catalyst under microwave irradiation furnished 1-{4ʹ-[3-chloro-2-(substituted phenyl)-4-oxo-azetidin-1-yl]-biphenyl-4-yl}-7-hydroxy-4-methyl-1H-quinolin-2-one (4a-j). Purity of synthesized compounds was checked by TLC and the structures were elucidated by their IR, 1H NMR, Mass and elemental analysis data. The synthesized compounds were screened for anticonvulsant activity.